The nationwide trends in hospital admissions, deaths, and costs related to hepatitis C stratified by psychiatric disorders and substance use: an analysis of US hospitals between 2016 and 2019. Issue 4 (23rd April 2023) - Lee, David Uihwan; Ponder, Reid; Lee, Ki Jung; Yoo, Ashley; Fan, Gregory Hongyuan; Jung, Daniel; Chou, Harrison; Lee, Keeseok; Hofheinz, Olivia; Urrunaga, Nathalie Helen
Abstract : Background and aims: Hepatitis C virus (HCV) is a prominent liver disease that often presents with mental illness. We stratify the HCV population and review its healthcare burden on the US hospital system. Methods: The US National Inpatient Sample was used to select admissions related to HCV between 2016 and 2019. Weights were assigned to discharges, and trend analyses were performed. Strata were formed across demographics, comorbidities, psychiatric and substance use conditions, and other variables. Outcomes of interest included hospitalization incidences, mortality rates, total costs, and mean per-hospitalization costs. Results: From 2016 to 2019, there were improvements in mortality and hospitalization incidence for HCV, as well as a decline in aggregate costs across the majority of strata. Exceptions that showed cost growth included admissions with multiple psychiatric, stimulant use, or poly-substance use disorders, and a history of homelessness. Admissions with no psychiatric comorbidities, admissions with no substance use comorbidities, and admissions with housing and without HIV comorbidity showed decreasing total costs. Along with per-capita mean costs, admissions with comorbid opioid use, bipolar, or anxiety disorder showed significant increases. No significant trends in per-capita costs were found in admissions without mental illness diagnoses. Conclusions: Most strata demonstrated decreases in hospitalization incidences and total costs surrounding HCV; however, HCV cases with mental illness diagnoses saw expenditure growth. Cost-saving mechanisms for these subgroups are warranted.